Genome-Wide Insights into the Development and Function of Thermogenic Adipocytes. (February 2017) - Loft, Anne; Forss, Isabel; Mandrup, Susanne
Abstract : Brown and brown-like adipocytes are specialized adipocytes with a high capacity to convert metabolic energy to heat. This function is not only eminent in supporting organismal thermogenesis, but may also have potential in the fight against obesity. The latter has spurred a massive interest in understanding the development and regulation of these thermogenic adipocytes. Here, we review how genome-wide studies based on next-generation sequencing have provided insight into how the chromatin and transcriptional landscapes are established in thermogenic adipocytes and how thermogenic signals can change the genomic programming of white adipocytes. Furthermore, we discuss how the integration of genomic data can be used to discover novel transcriptional pathways that may be modulated as part of therapeutic strategies for the treatment of obesity. Trends: The development and thermogenic functions of brown adipocytes are regulated by coordinated actions of many different transcription factors, cofactors, noncoding RNAs, and histone modifiers. Activation of thermogenic transcriptional regulators can change the genomic programming of white adipocytes and lead to the formation of brown-like adipocytes. Integrative genomic approaches allow deciphering of the transcriptional networks that control the development and specialized functions of thermogenic adipocytes. Integrative genomic approaches may reveal novel transcriptional pathways that can be targeted to increase the thermogenic capacity of adipocytes.